IMPLEMENTASI METODE SAW (SIMPLE ADDITIVE WEIGHTING) SEBAGAI PENDUKUNG KEPUTUSAN UNTUK REKOMENDASI HABITAT KELINCI BERBASIS IoT (INTERNET OF THINGS) - Anderias Eko Wijaya; Nur Imam Iskandar (STMIK SUBANG, 2020)
Rabbits are mammals from the family Leporidae (green plant eaters) which can be found in many parts of the earth. Rabbits are very susceptible to temperature changes. Temperature greatly affects the rabbit's body metabolism. The temperature ideal for rabbits is in the range of 60 – 650F or equal to 15.5 - 18.30C temperature is known as